A multifaceted comparison between the fruit-abscission and fruit-retention cultivars in ornamental crabapple - Wang, Xue; Wang, Yi; Yan, Shufang; Sun, Xuan; Liu, Hongyan; Cheng, Beibei; Xu, Xingxing; Wei, Zunzheng; Zhang, Guojun (Frontiers in Plant Science, 2022)
The ornamental crabapple is a multipurpose landscaping tree that bears brilliant fruit throughout the winter. However, whether or not its fruit persists after maturation is specifically correlated to cultivar characteristics. In this work, we screened two different types that display fruit-retention (‘Donald Wyman’, ‘Red Jewel’, and ‘Sugar Tyme’) and fruit-abscission (‘Radiant’ and ‘Flame’) in northern China across the whole winter using multi-year successional records. Fruit-abscission was determined predominantly by the abscission zone established at the base of the pedicel, regardless of fruit size and pedicel length, according to the results of the comparative research. The primary physiological rationale was the accumulation of hydrolases activity (pectinesterase, cellulase, polygalacturonase and β-glucosidase). Comparative transcriptomics further identified a number of up-regulated DEGs involved in the synthesis pathways of canonical phytohormones such as ethylene, jasmonic acid, abscisic acid and cytokinin, as well as 12 transcription factors linked in downstream signaling in fruit-abscission cultivars. Finally, a model incorporating multi-layered modulation was proposed for the fruit abscission of ornamental crabapple. This study will serve as the foundation for the development of fruit-viewing crabapples that have an extended ornamental lifetime.